Phenomenology of Religious Thought in Public Universities in The Study of Sociology and Anthropology - Nuryadin, Nuryadin; Norlaila, Norlaila; Mudhiah, Mudhiah; Emroni, Emroni (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This study aims to examine the differences between religious education at the school and university levels, focusing on the curriculum, sources of religious knowledge, and the role of media in shaping students' religious understanding. The research employs a qualitative approach, utilizing document analysis and interviews with students at Lambung Mangkurat University (ULM) in Banjarmasin. The findings reveal that university-level religious education in Islamic studies deepens students' understanding of religious concepts, emphasizing moral and spiritual aspects. The study also highlights the pivotal role of parents in instilling religious values from an early age and the significant influence of social media, with Ustadz Adi Hidayat being a popular religious figure among students. Moreover, ULM students predominantly possess a textualist scripturalist understanding of religious diversity, primarily focusing on exoteric-shariah aspects. The research contributes to discussions on the dynamics of religious education and the diverse sources shaping students' religious knowledge.